2020
DOI: 10.1177/1539449220905813
|View full text |Cite
|
Sign up to set email alerts
|

Independent Older Adult’s IADL and Executive Function According to Cognitive Performance

Abstract: Participation in Instrumental Activities of Daily Living (IADL) is essential in occupational therapy aiming to improve the life situation of elderly. Effective executive function (EF) is important to successful functioning in IADL. The purpose of this study was to examine EF and IADL performance differences according to cognitive levels as measured by the Montreal Cognitive Assessment (MoCA), age, and gender. In all, 80 elderly (49% female; age M = 73.4) were assessed at home, with Weekly Calendar Planning Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
4
15
0
3
Order By: Relevance
“…Because we did not have a detailed cognitive assessment to which we could compare WCPA-10 performance, the specific cognitive impairments contributing to deficient performance are unknown. However, prior research has demonstrated an association between the 17-item WCPA and executive functions (17,19,20), suggesting that executive dysfunction may have impacted performance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because we did not have a detailed cognitive assessment to which we could compare WCPA-10 performance, the specific cognitive impairments contributing to deficient performance are unknown. However, prior research has demonstrated an association between the 17-item WCPA and executive functions (17,19,20), suggesting that executive dysfunction may have impacted performance.…”
Section: Discussionmentioning
confidence: 97%
“…The task of entering appointments into a weekly schedule is easily recognized as relevant to functional abilities in everyday life and appears easy on the surface; however, appointment conflicts, rule constraints and unexpected obstacles create significant cognitive challenges that require a strategic approach. The standard 17-item version of the WCPA differentiates between healthy controls and a wide range of populations with executive dysfunction including those with multiple sclerosis ( 19 ), mild cognitive impairment ( 20 ), attention-deficit hyperactivity disorder ( 21 ), pediatric acquired brain injury ( 22 ), and epilepsy ( 23 ). Accuracy on the WCPA correlates with inhibitory control and set-shifting as assessed by the Delis-Kaplan Executive Functioning System ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The shorter, 10 item version of the WCPA (WCPA-10) differs from the WCPA-17 only in the number of appointments required to schedule and has an important advantage of taking less time to administer. The WCPA-10 differentiates between healthy adults and individuals' post-stroke (Jaywant et al, 2021) or with MCI (Lahav and Katz, 2020). Lahav and Katz (2020) also reported declining IADL performance in participants with MCI compared with healthy controls although the correlation between IADL performance and WCPA-10 performance was not reported.…”
Section: Introductionmentioning
confidence: 92%
“…The WCPA-10 differentiates between healthy adults and individuals' post-stroke (Jaywant et al, 2021) or with MCI (Lahav and Katz, 2020). Lahav and Katz (2020) also reported declining IADL performance in participants with MCI compared with healthy controls although the correlation between IADL performance and WCPA-10 performance was not reported.…”
Section: Introductionmentioning
confidence: 92%
“…It also assesses a person’s cognitive strategy use in facilitating efficient performance. The standard 17-item version of the WCPA differentiates between healthy controls and a wide range of populations with executive dysfunction including those with multiple sclerosis (12), mild cognitive impairment (13), attention-deficit hyperactivity disorder (14), pediatric acquired brain injury (15), and epilepsy (16). It is responsive to change in executive functions in individuals with schizophrenia undergoing a metacognitive cognitive rehabilitation program (17).…”
Section: Introductionmentioning
confidence: 99%